The Association Between Reading the Mind in the Eyes Test Performance and Intelligence Quotient in Children and Adolescents With Asperger Syndrome - Peñuelas-Calvo, Inmaculada; Sareen, Aditya; Porras-Segovia, Alejandro; Cegla-Schvatzman, Fanny-Beatriz; Fernandez-Berrocal, Pablo (Frontiers in Psychiatry, 2021)
Background: There has been an extensive debate about a potential association between intelligence and social cognition. In this study, we aimed to assess the association between social cognition as measured with the Reading the Mind in the Eye Test (RMET) and intelligence as measured with Fourth Edition of the Wechsler Intelligence Scale for Children (WISC-IV) in children and adolescents diagnosed with Asperger Syndrome (AS). Methods: We conducted a cross-sectional study among 84 children diagnosed with AS aged 6-16 years (Mean= 11.64 Standard Deviation= 2.75; 92.9% males). We analyzed the association between RMET performance and WISC-IV total score, as well as the association between RMET performance and each of the four WISC-IV indexes (Processing Speed Index, PSI; Working Memory Index, WMI; Perceptual Reasoning Index, PRI, and Verbal Comprehension Index, VCI). Results: We found a positive correlation between RMET performance and FSIQ (r=0.340 p< 0.01), VCI (r= 0.310 p< 0.01), PRI (r=0.401 p< 0.01), and WMI (r=0.292 p< 0.01). In the multivariate logistic regression model, age was a significant predictor of RMET score (β =0.250, OR=1.28, 95% CI= 1.04-1.58, p=0.018), as was PRI (β = 0.044, OR=1.045, 95% CI=1.01-1.08, p=0.018). Conclusion: Our results suggest that intelligence quotient positively influences RMET performance, indicating that intelligence increases social cognition in individuals diagnosed with AS. However, weak-to-moderate size effects were found. This study contributes to understanding the mechanisms underlying the disturbance of social cognition in children and adolescents diagnosed with AS.